Reading, investment, and guarantee: The Pale King and the authority of the modern literary archive. Issue 5 (4th May 2022) - Roache, John
ABSTRACT: This article argues that an analysis of David Foster Wallace's unfinished and posthumously published novel The Pale King, alongside its various drafts and 'genetic' materials, can illuminate a series of important contradictions underlying conventional theories of and approaches to the modern literary archive. A number of scholars have noted the paradox of authority that informs any author's archive: it can be read either as a trace of original artistic creativity, or as a repository of 'waste materials' which failed to survive the revisionary process. However, in Wallace's novel and its manuscript variants, there is a sustained attempt to resolve this dichotomy by appealing to the mediatory figure of the author 'himself': that is to say, to a narrator called 'David Wallace' who, in a kind of uncanny collaboration with the actual, historical Wallace, purports to write and revise the narrative in front of our very eyes. This article contends that the resulting oscillations between the text and its genetic variants help simultaneously to construct and to scrutinise an economic model of the literary archive based upon labour and investment, which in turn facilitates a self-reflexive critique of the rapidly increasing valorisation of archival labour within the neoliberal university system.